2023
DOI: 10.1021/acsami.3c08614
|View full text |Cite
|
Sign up to set email alerts
|

Highly Water-Stable and Efficient Hydrogen-Producing Heterostructure Synthesized from Mn0.5Cd0.5S and a Zeolitic Imidazolate Framework ZIF-8 via Ligand and Cation Exchange

Abstract: Developing highly water-stable zeolitic imidazolate frameworks (ZIFs) for visible-light-driven photocatalytic hydrolysis is important and challenging. Herein, the Type II heterojunction catalyst Mn0.5Cd0.5S@ZIF-8 and its derivatives (including MCS@ZIF-8-Mn, MCS@ZIF-8-Br, and MCS@ZIF-8-MB) were successfully constructed using a facile strategy. Through dual postsynthetic ligand and cation exchange (PSE) treatments of Mn(Ac)2·4H2O and 4-bromo-1H-imidazole for ZIF-8, the hydrogen production efficiency of the MCS@Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…However, this change is small, indicating an indirect effect. Two obvious peaks on the high-resolution spectrum (Figure d) of Zn 2p in the sample QDs@ZIF-67/ZIF-8 are located at 1045.28 and 1022.18 eV, attributed to Zn 2p 1/2 and Zn 2p 3/2 , respectively, which shows positive deviation than those reported in the literature. After careful inspection of the spectrum of Co 2p (Figure e), it was found that two other companion peaks appeared in addition to the two characteristic peaks, Co 2p 1/2 and Co 2p 3/2 . Two distinct peaks in the sample QDs@ZIF-67/ZIF-8 are located at 797.08 and 781.08 eV, while the corresponding two peaks in sample QDs@ZIF-67 are located at 796.78 and 781.18 eV.…”
Section: Resultssupporting
confidence: 88%
“…However, this change is small, indicating an indirect effect. Two obvious peaks on the high-resolution spectrum (Figure d) of Zn 2p in the sample QDs@ZIF-67/ZIF-8 are located at 1045.28 and 1022.18 eV, attributed to Zn 2p 1/2 and Zn 2p 3/2 , respectively, which shows positive deviation than those reported in the literature. After careful inspection of the spectrum of Co 2p (Figure e), it was found that two other companion peaks appeared in addition to the two characteristic peaks, Co 2p 1/2 and Co 2p 3/2 . Two distinct peaks in the sample QDs@ZIF-67/ZIF-8 are located at 797.08 and 781.08 eV, while the corresponding two peaks in sample QDs@ZIF-67 are located at 796.78 and 781.18 eV.…”
Section: Resultssupporting
confidence: 88%
“…Zeolite is widely used in pollutant control, petrochemistry, water purification, gas purification, and other fields because of its excellent catalytic ability, cation exchange ability, and adsorption ability [ 1 , 2 , 3 , 4 ]. The main chemical components of fly ash are silica and alumina, which are similar to zeolite [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%